STUDIES ON DISTRIBUTION AND DIVERSITY OF CHIRONOMID LARVAE (INSECTA: DIPTERA), WITH RESPECT TO WATER QUALITY IN SALIM ALI LAKE, AURANGABAD, INDIA - P. R. BHOSALE; R. J. CHAVAN; A. M. GAIKWAD (The Bioscan, 2012)
The distribution and diversity of chironomid larvae were investigated with respect to some physico-chemical parameters in Salim Ali Lake at Aurangabad (19º53’55’’N, 75º20’28’’E) to study the influence of physico- chemical parameters on Chironomidae larvae. Samples were collected from five sites of lake in each month over a period of one year, from Oct. 2009 to Sept. 2010. Total of 9 taxa belonging to two sub-families, Chironominae and Tanypodinae were observed. Chironominae was dominant for both richness and evenness, the frequent and abundant genus was Chironomus. The mean density of chironomid larvae during period of study was 1771 larvae/m2. According to Shannon- Wiener diversity index Salim Ali lake has average diversity 0.57. Furthermore, according to Pearson correlation index density of chironomid larvae does not significantly correlates with studied ecological parameters of lake water.